What is to be expected from an ethics audit integrated within the accreditation process of hospitals from romania? - Daniela Tatiana Agheorghiesei; Liliana Iliescu; Cristina Gavrilovici; Liviu Oprea (Tehran University of Medical Sciences, 2013)
We aimed to verify the issue of the ethics audit and its use in the system of accreditation of hospitals. It presents the results of a survey conducted among hospital managers from Romania.Our article highlights the results of the second part of a research carried out in 2012 on the pertinence and the structure of the ethics audit integrated within the accreditation process of hospitals, according the opinion of the 47 executives and managers involved in the quality management of Romania hospitals. The data have been gathered with the aid of the online questionnaire.An ethics audit integrated within the accreditation process of hospitals should include primarily the respect of the patients' rights, the good relations of the institutions with its patients and the respect of the moral rights of the employees.The usefulness of this study is due to the fact that it consults precisely those who should really contribute to the creation, application and monitoring of ethical policies and instruments necessary in every hospital which are permanently under the scrutiny of public opinion and confront themselves with the obligation to give a thorough account of their results and spending of the public resources. This study gain consistency as the relevant aspects that could form the structure of a hospital ethics audit are identified with the direct help of the managers responsible for implementing it.